Nanocellulose‐Based Antibacterial Materials. Issue 20 (19th June 2018) - Li, Juanjuan; Cha, Ruitao; Mou, Kaiwen; Zhao, Xiaohui; Long, Keying; Luo, Huize; Zhou, Fengshan; Jiang, Xingyu
Abstract: In recent years, nanocellulose‐based antimicrobial materials have attracted a great deal of attention due to their unique and potentially useful features. In this review, several representative types of nanocellulose and modification methods for antimicrobial applications are mainly focused on. Recent literature related with the preparation and applications of nanocellulose‐based antimicrobial materials is reviewed. The fabrication of nanocellulose‐based antimicrobial materials for wound dressings, drug carriers, and packaging materials is the focus of the research. The most important additives employed in the preparation of nanocellulose‐based antimicrobial materials are presented, such as antibiotics, metal, and metal oxide nanoparticles, as well as chitosan. These nanocellulose‐based antimicrobial materials can benefit many applications including wound dressings, drug carriers, and packaging materials. Finally, the challenges of industrial production and potentials for development of nanocellulose‐based antimicrobial materials are discussed. Abstract : The current state of research and future development of nanocellulose in antibacterial applications are mainly outlined. The fabrication of nanocellulose‐based antimicrobial materials for wound dressings, drug carriers, and packaging materials is the focus of this research. There are mainly four methods for preparing nanocellulose‐based antimicrobial materials, containing surface modification, antibiotic addition, combination with nanomaterials, and combination with antibacterial polymers.